Suicide Ideation and Patterns among Suicide Survivors Admitted in Teaching Tertiary Care Hospital Multan, South Punjab Pakistan (Journal of Fatima Jinnah Medical University, 2024)
Background: Suicide, defined as a fatal self-injurious act with intent to die, is a significant public health concern worldwide. Loneliness, depression, and trauma are linked to suicidal ideation, and methods of suicide vary across regions. This study focuses on evaluating factors influencing suicidal ideation and behavior in a tertiary care hospital in Punjab, Pakistan.Subject and Method: A quantitative survey was completed as part of a cross-sectional study among patients who had attempted suicide in order to determine the magnitude of suicidal ideation and behavior. A pre-tested questionnaire was employed, and a random sample of 62 people was used. The data was compiled, assembled, and jotted down using Google Forms. Data analysis and computation have been done via SPSS version 22.Result: An examination of the data revealed and unacceptably high occurance of suicide.( prevalence)  The majority felt life was not worth living, and many believed their families would be happier without them. Thoughts like "You’ll be sorry when I’m gone" were common, and 48 survivors had the thought "I won’t be in your way much longer" before attempting suicide. Another frightening factor was that most of the patients were in their early twenties.Conclusion: The findings reveal high rates of suicidal thoughts among survivors of suicide attempts. Factors include hopelessness and a lack of understanding. So, there is a dire need for proper counselling and early recognition of problems. Comprehensive suicide prevention strategies and mental health support systems are crucial to addressing risk factors and providing effective intervention.
Keywords: Suicidal thoughts and ideation; self-harm; suicide; youth; mental health problems